(untitled) (International Journal of Engineering and Computer Science, 2024)
This article analyzes the vulnerabilities of the Content Security Policy (CSP) standard with the aim of improving website security. It highlights that this standard has vulnerabilities that enable attackers to successfully execute attacks by injecting malicious code into web pages. The relevance of studying CSP vulnerabilities to enhance website protection is substantiated. The primary aspects of implementing web resource protection using the CSP standard are discussed. The article outlines the most well-known techniques for bypassing the directives of this standard. It describes the process of executing an XSS attack using the "unsafe-inline" directive. It is revealed that such an attack organization allows the interception of user data without detection by users or security administrators. The conclusion is made that the use of the unsafe-inline directive by developers does not provide an adequate level of protection against XSS attacks. As an alternative, the implementation of a more effective CSP policy, configured in accordance with the recommendations of information security specialists, is proposed.